Intrapatient viral diversity and treatment outcome in patients with genotype 3a hepatitis C virus infection on sofosbuvir‐containing regimens. Issue 4 (28th December 2017) - Bhardwaj, N.; Ragonnet‐Cronin, M.; Murrell, B.; Chodavarapu, K.; Martin, R.; Chang, S.; Miller, M. D.; Feld, J. J.; Sulkowski, M.; Mangia, A.; Wertheim, J. O.; Osinusi, A.; et al.
Summary: Treatment with the direct‐acting antiviral agent (DAA) sofosbuvir (SOF), an NS5B inhibitor, and velpatasvir (VEL), an NS5A inhibitor, demonstrates viral cure rates of ≥95% in hepatitis C virus (HCV) genotypes (GT) 1‐6. Here, we investigated intrapatient HCV diversity in NS5A and NS5B using Shannon entropy to examine the relationship between viral diversity and treatment outcome. At baseline, HCV diversity was lowest in patients infected with HCV GT3 as compared to the other GTs, and viral diversity was greater in NS5A than NS5B ( P < .0001). Treatment outcome with SOF/VEL or the comparator regimen of SOF with ribavirin (RBV) was not correlated with baseline diversity. However, among persons treated with SOF/VEL, a decrease in diversity from baseline was observed at relapse in the majority virologic failures, consistent with a viral bottleneck event at relapse. In contrast, an increase in diversity was observed in 27% of SOF+RBV virologic failures. We investigated whether the increase in diversity was due to an increase in the transition rate, one mode of potential RBV‐mediated mutagenesis; however, we found no evidence of this mechanism. Overall, we did not observe that viral diversity at baseline influenced treatment outcome, but the diversity changes observed at relapse can improve our understanding of RBV viral suppression in vivo.